Mursun ja norsun jäljillä - Häkkinen, Kaisa (Kotikielen Seura, 2007)
Tracing the etymology of mursu ’walrus’ and norsu ’elephant’ (englanti)4/2007 (111)TRACING THE ETYMOLOGY OF MURSU WALRUS AND NORSU ELEPHANTThe words that Finnish has borrowed from Saami are mainly related to Lapland. One exception is norsu elephant, which is etymologically the same word as mursu walrus. Common to these two animal species are their large tusks, which have been a highly valued trading item. Norsunluu ivory was mentioned as far back as the sixteenth-century, in the works of Mikael Agricola.Neither the walrus nor the elephant have ever been part of Finlands fauna. They have been recognised only via literature or hearsay, and this has contributed to variation in the phonetic form of the loanword for this unfamiliar referent: mursa, mursu, norsu, nursa, nursu. The word was finally established in the written language as two different lexemes, mursu and norsu.In Finnish dialects, mursu and norsu have, for the most part, been animal names learned from standard written Finnish. Interestingly, dialect data for mursunnahka walrus hide is more extensive than for the word mursu, because walrus-hide straps were once a familiar trading item. As a dialect word, norsu is only marginal, but in certain central Ostrobothnian dialects it is the name for a walrus.Elephants and ivory were known among the great civilisations of the Mediterranean region from ancient times, whereas the walrus was for long a mystery, even to scholars. Before the era of large sailing ships, seafarers scarcely ventured as far north as to encounter creatures of the Arctic oceans. Monsters were believed to inhabit the fringes of the known world. One of these was rosmarus piscis (lit. walrus fish), which was illustrated in Olaus Magnuss Carta Marina, the earliest map of the Nordic countries, in 1539.Although the word mursu, in its current form and meaning, was referred to by Henrik Gabriel Porthan as long ago as the 1770s, it was later occasionally still known as a shark or large fish. Information on another creature, the mammoth, has also ...